Neurocognitive outcomes in pediatric patients following brain irradiation - Kozyra, Katharina; Lüttich, Peggy; Regnery, Sebastian; König, Laila; Bernhardt, Denise; Witt, Olaf; Herfarth, Klaus; Unterberg, Andreas; Jungk, Christine; Farnia, Benjamin; Combs, Stephanie; Debus, Jürgen; et al. (Cancers, 2021)
Advanced radiation techniques can reduce the severity of neurocognitive sequelae in young brain tumor patients. In the present analysis, we sought to compare neurocognitive outcomes after proton irradiation with patients who underwent photon radiotherapy (RT) and surgery. Neurocognitive outcomes were evaluated in 103 pediatric brain tumor patients (proton RT n = 26, photon RT n = 30, surgery n = 47) before and after treatment. Comparison of neurocognitive outcomes following different treatment modalities were analyzed over four years after treatment completion. Longitudinal analyses included 42 months of follow-up after proton RT and 55 months after photon RT and surgery. Neurocognitive assessment included standardized tests examining seven domains. A comparison of neurocognitive outcomes after RT (proton and photon with >90% additional surgery) and surgery showed no significant differences in any neurocognitive domain. Neurocognitive functioning tests after proton RT failed to identify alterations compared to baseline testing. Long-term follow up over four years after photon RT showed a decrease in non-verbal intelligence (−9.6%; p = 0.01) and visuospatial construction (−14.9%; p = 0.02). After surgery, there was a decline in non-verbal intelligence (−10.7%; p = 0.01) and processing speed (14.9%; p = 0.002). Differences in neurocognitive outcomes between RT and surgical cohorts in direct intermodal comparison at long-term follow-up were not identified in our study, suggesting that modern radiation therapy does not affect cognition as much as in the past. There were no alterations in long-term neurocognitive abilities after proton RT, whereas decline of processing speed, non-verbal intelligence, and visuospatial abilities were observed after both photon RT and surgery. Domains dependent on intact white matter structures appear particularly vulnerable to brain tumor treatment irrespective of treatment approach.